Floating door sign does not differentiate Parkinson’s disease from essential tremor - Räty, Valtteri (My University, 2024)
Parkinson’s disease (PD) is known to be associated with micrographia, presented as decreased letter size in written text. A previous reported, potentially important observation suggested that when PD patients are instructed to draw a house, patients undershoot the drawing of the vertical lines of the door of the house and fail to connect the lines with the house floor. This ‘floating door sign’ would be a result of shortened stroke size and hypometric hand movements in PD and, importantly, no similar findings were reported in patients with essential tremor (ET). Thus, the sign could represent a simple qualitative test for PD vs ET differential diagnostics. In this study, we evaluated the usefulness of the floating door sign as a bedside test in early PD diagnostics compared to ET patients and healthy controls (HC). We advised the subjects (XX PD patients, XX ET patients and XX healthy controls) to draw a house with windows and a door. We then measured the distance between the horizontal floorline of the house to the vertical doorlines. The results showed that there was no difference in the presence of the floating door sign between PD and ET patients, as 47% of PD patients and 37% of ET patients presented the sign (p=0.26). Compared to healthy controls, PD patients showed more floating door sign (PD: 47% vs. HC: 24% p<0.05) but there were no differences between ET patients and healthy controls. In conclusion, the floating door sign does not differentiate PD from ET and is not a valid bedside test for clinicians.
Keywords: Parkinson disease, Essential tremor, Neurology, Movement disorder, floating door